MAIT cells in health and disease - Provine, NM; Klenerman, P (Annual Reviews, 2020)
Mucosal-associated invariant T (MAIT) cells have been attracting increasing attention over the last few years as a potent unconventional T cell subset. Three factors largely account for this emerging interest. Firstly, these cells are abundant in humans, both in circulation and especially in some tissues such as the liver. Secondly is the discovery of a ligand that has uncovered their microbial targets, and also allowed for the development of tools to accurately track the cells in both humans and mice. Finally, it appears that the cells not only have a diverse range of functions but also are sensitive to a range of inflammatory triggers that can enhance or even bypass T cell receptor–mediated signals—substantially broadening their likely impact in health and disease. In this review we discuss how MAIT cells display antimicrobial, homeostatic, and amplifier roles in vivo, and how this may lead to protection and potentially pathology.